Pengenalan Bahasa dan Budaya Jepang Bagi Guru dan Siswa - Diana Kartika; Yuni Astuti; Yusrizal Bakar; Ali Mardius (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The purpose of the introduction of Japanese language and cultural recognition for teachers and students of SMA Xaverius Bukittinggi is that students understand from the beginning that to be able to master and communicate using Japanese language well is not enough to master only four language skills (listening, speaking, reading and writing) Should be able to understand Japanese culture. If you can use Japanese and understand Japanese culture well, then communication misconceptions with Japanese people can be minimized. Therefore, learning Japanese language academically also requires the process of learning Japanese culture.